Perlindungan Hukum Terhadap Pekerja Alih Daya Pasca Berlakunya Undang-Undang Nomor 6 tahun 2023 - Dewa Gede Doni Anggara Pramudia; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (Fakultas Hukum, Universitas Warmadewa, 2026)
This research examines legal protection for contract workers following the enactment of Law Number 6 of 2023. The background of this research highlights the persistent violations of contract workers' rights in Indonesia, caused by weak legal regulations. The research questions address how legal protection can be provided for contract workers and the rights of those who have reached retirement age. The objective of this study is to analyze legal protection and the rights of contract workers. The expected benefit of this research is to contribute both theoretically and practically to the development of labor law. The research method used is normative legal research with a legislative approach. The results indicate that changes in the Job Creation Law have weakened protections for contract workers, particularly by removing limitations on the types of jobs that can be outsourced. The conclusion of this study emphasizes the need for regulatory revisions to strengthen the protection of workers' rights. Recommendations include enhancing government oversight and raising awareness about legal protections for contract workers.